Stokiometri Karbon (C), Nitrogen (N) dan Fosfor (P) Tanah pada Pengelolaan Jerami dan Irigasi Sawah - Alviyanti, Vivi; Sulastri, Ni Nyoman; Sumiyati, Sumiyati; Tika, I Wayan; Ngadisih (Jurnal BETA (Biosistem dan Teknik Pertanian), 2025)
Rice farming requires a sustainable management strategy to maintain soil quality and water use efficiency. The habit of burning straw and inundation irrigation that is predominantly used by farmers often reduces soil quality and nutrient balance. This study aimed to determine the dynamics of C:N:P stochiometry in straw management and irrigation management during one planting season and determine the best treatment combination for changes in C:N:P stochiometry. The study was conducted in Subak Suala, Bali, using a random design complete with two factors: irrigation management (ngenyatin, inundation, and Alternating Wetting and Drying - AWD) and straw management (burning and planting straw). Data were obtained through soil sampling on 30 treatment plots, tested in the laboratory and the results were analyzed using the two-way ANOVA test to evaluate the combination of irrigation treatment and hay management to the C:N:P ratio of soil. The Z test is used to determine the difference in the average ratio of CN, CP and NP before and after treatment. The results of the data analysis showed that the CN ratio ranged from 3.81– 17.50 with the largest decrease (40%) in inundation irrigation and straw immersion. The CP ratio ranges from 8.83–47.16 and decreases more significantly (50%) in AWD irrigation and straw burning. The NP ratio ranged from 0.75–4.77 with the largest decrease (46%) in AWD irrigation and straw burning, as well as a small increase (5%) in ngenyatin irrigation and straw immersion. This study proves that straw immersion is more effective in maintaining carbon and nitrogen balance than burning straw, while AWD irrigation systems are more optimal in maintaining the availability of phosphorus. A combination of straw planting and an AWD irrigation system is recommended to support sustainable land productivity in Subak